Amino acid-based Poly(ester urea) copolymer films for hernia-repair applications. (November 2018) - Dreger, Nathan Z.; Fan, Zhaobo; Zander, Zachary K.; Tantisuwanno, Chinnapatch; Haines, Molly C.; Waggoner, Morgan; Parsell, Trenton; Søndergaard, Claus S.; Hiles, Michael; Premanandan, Christopher; Becker, Matthew L.
Abstract: The use of degradable materials is required to address current performance and functionality shortcomings from biologically-derived tissues and non-resorbable synthetic materials used for hernia mesh repair applications. Herein a series of degradable l -valine- co - l -phenylalanine poly(ester urea) (PEU) copolymers were investigated for soft-tissue repair. Poly[(1-VAL-8)0.7 - co -(1-PHE-6)0.3 ] showed the highest uniaxial mechanical properties (332.5 ± 3.5 MPa). Additionally, l -valine-co- l -phenylalanine poly(ester urea)s were blade coated on small intestine submucosa extracellular matrix (SIS-ECM) and found to enhance the burst test mechanical properties of SIS-ECM in composite films (force at break between 102.6 ± 6.5–151.4 ± 11.3 N). Free standing films of l -valine- co - l -phenylalanine PEUs were found to have superior extension at break when compared to SIS-ECM (averages between 1.2 and 1.9 cm and 1.2 cm respectively). Fibroblast (L-929) spreading, proliferation, and improved attachment over control were observed without toxicity in vitro, while a reduced inflammatory response at both 7 and 14 days post-implant was observed for poly[(1-VAL-8)⁠0.7 -co-(1-PHE-6)⁠0.3 ] when compared to polypropylene in an in vivo rat hernia model. These results support the use of PEU copolymers as free-standing films or as composite materials in soft-tissue applications for hernia-repair.